Application Of C4.5 Algorithm In Disease Classification - Barutu, Sipra (Journal Of Data Science, 2024)
In the modern era, information and communication technology (ICT) has a significant impact on the health sector, one of which is through the application of artificial intelligence (AI) for disease diagnosis. The C4.5 algorithm, one of the popular classification algorithms, shows great potential in helping doctors classify diseases more accurately and efficiently. Research shows that the C4.5 algorithm is able to achieve a high level of accuracy in classifying various types of diseases, such as diabetes mellitus, heart disease, and lung disease. Its advantages include ease of interpretation, resistance to data noise, and efficiency. However, its application also has several challenges, such as the availability of quality data, complex interpretation of results, and the potential for overfitting. Nevertheless, the C4.5 algorithm offers great potential to improve the quality of patient diagnosis and care. Further research is needed to overcome the challenges and improve the effectiveness of the C4.5 algorithm in disease classification, such as the development of anti-overfitting techniques, optimal attribute selection methods, and application to more types of diseases. With continued research and development, the C4.5 algorithm can become a valuable tool for doctors and other medical personnel in fighting disease.